FAKTOR YANG BERHUBUNGAN DENGAN PRODUKTIVITAS KERJA PERAWAT DI RUMAH SAKIT UMUM DAERAH PETALA BUMI PROVINSI RIAU TAHUN 2017: work productivity - WAN INTAN PARISMA (STIKes Al-Insyirah Pekanbaru, 2018)
Still encountered several problems in work productivity. Based on interviews with several nurses found problems in terms of work productivity such as errors in the recording of patient documentation, undisciplined working hours, the relationship between work teams that have not maximized, the dissatisfaction in providing incentives and training problems that are not sufficient standards. Therefore, this study aims to determine the factors associated with work productivity of nurses in the inpatient room of Rumah Sakit Umum Daerah Petala Bumi Riau Province in 2017 based on work environment, supervision, training and incentive.This research is quantitative analytic observational with cross sectional design type of cross sectional study. The number of samples in this study were nurses who fulfilled the exclusion criteria of 57 people. Univariate and bivariate data analysis technique with chi square test, followed by multivariate test using multiple logistic regression.From the results of bivariate analysis related to work productivity of nurses in the inpatient room is the work environment, supervision and training. While incentives have no relationship to work productivity of nurses. From the result of multivariate analysis, the most influencing variable on the work productivity of the nurses in the inpatient room is training (OR: 17,5, 95% CI 1.42-216,6) and work environment as confounding variable.For that need to make improvements and addition of physical facilities to develop and improve the work performance of nurses, more attention to the head of the room in applying supervision as an alternative for the nurse to achieve work productivity by conducting proper training to the nurse, in order to create a climate and work atmosphere more good, and reduce the incidence of accidents due to work.